Sidekicks - Santat, Dan. (New York, N.Y. : Arthur A. Levine Books, 2011)
When Captain Amazing feels he is getting too old to be a reliable superhero, he tries to hire a new sidekick, but his pets have different ideas.
Accelerated Reader AR
MSBA Nominee 2012-13.
Keywords: Superheroes -- Comic books, strips, etc; Heroes -- Comic books, strips, etc; Pets -- Comic books, strips, etc; Graphic novels; Graphic novels